الوظائف الإيقاعية والدلالية لأنماط التكرار في القصيدة المحمدية للبوصيري (Al-Farooq Journal of Sciences, 2026)
This research delves into the semantic and rhythmic functions of repetition in Al-Busiri’s Al-Qasida Al-Muhammadiyya, illuminating how this device transcends mere rhetorical embellishment to emerge as a pivotal stylistic architecture. The study examines diverse repetitive patterns, ranging from the traditional recurrence of meter and rhyme inherent in classical Arabic poetry, to the invocation of the Prophet’s name (Peace Be Upon Him) at the dawn of each verse—a technique that breathes a unique spiritual cadence into the poem and deepens its semantic resonance. Furthermore, the paper analyzes the facets of repetition within syntactic parallelism, encompassing morphological, structural, and grammatical forms, thereby underscoring their vital role in shaping the text and amplifying its emotional profoundness. Ultimately, the research concludes that the poem's enduring power stems from the organic fusion of its form and essence, masterfully woven through the art of repetition."
Keywords: Syntactic Parallelism, Prophetic Panegyric, Inner Cadence, Morphological Architecture, Psychological Resonance.